Relationship between Anxiety Level and Hypertension in the Elderly - Aries Rusmadi; Badar; Siti Nuryanti (Asian Journal of Healthcare Analytics, 2023)
Hypertension is a deadly chronic disease that is often referred to as a silent killer. The elderly who have various conditions and degenerative diseases that may suffer, of course, all the information that is circulated and received has an influence on the status of stress and anxiety levels in the elderly. The purpose of this study was to determine the relationship between anxiety levels and the incidence of hypertension in the elderly in the UPT work area. Long Laai Community Health Center, Segah District, Berau District. This research is an observational analytic study with a cross sectional approach. This research was conducted in all UPT working areas. Long Laai Health Center. Measuring tool used in the form of a questionnaire and data analysis using the Chi-Square test. The results of the analysis and discussion show that there is a significant relationship between the level of anxiety and the incidence of hypertension in the elderly in the working area of ​​the UPT. Long Laai Community Health Center, Segah District, Berau Regency.